UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA KELAS VIII SMPN 2 TANJUNG MUTIARA DENGAN PENGGUNAAN MEDIA POWERPOINT INTERAKTIF - Hastuti, Tri Lusni (Program Studi Pendidikan Biologi FKIP Unpatti, 2022)
The use of learning media in science learning is still lacking which causes students to tend to be passive and less enthusiastic in learning activities. This is evidenced by the low activity and student learning outcomes in science class VIII.2 at SMP Negeri 2 Tanjung Mutiara. This study aims to increase student activity and learning outcomes in science lessons by using interactive powerpoint media which was carried out in class VIII.2 with 26 students. This research was a classroom action research conducted in two cycles. From the results of the study, it was found that in cycle 1 the results of activity presentations were 43.6% and learning outcomes were 42%. While in cycle 2 there was an increase in activity to 79.4% and learning outcomes to 75.7%. So it can be said that the learning process using interactive powerpoint media can increase student activity and learning outcomes in science subjects for class VIII.